Fatigue and fracture strength of a multi-planar circular hollow section TT-joint. (February 2017) - Li, T.; Lie, S.T.; Shao, Y.B.
Abstract: A multi-planar circular hollow section (CHS) TT-joint with one brace subjected to axial tensile load and the other brace pinned is tested up to failure. The objectives include verifying the accuracy of S-N curves approach for predicting the fatigue life of the uncracked multi-planar CHS TT-joint and calculating the bearing capacity of the cracked multi-planar CHS TT-joint. The stress distributions along the weld toes at the two chord-brace intersection zones are measured first by carrying out a static test. It is found that the hot spot stress is located at one crown position of the chord. Subsequently, fatigue test using the alternating current potential drop (ACPD) technique is conducted to record the crack initiation and propagation through the chord thickness. It is found that crack initiates at the hot spot stress location, and the crack length versus the depth resembles a semi-ellipse in shape. The fatigue life of the TT-joint can be safely predicted using S-N curves incorporated in the CIDECT code. Finally, axial tensile load in displacement control mode is applied incrementally to the loaded brace end until the final failure occurs. Load displacement curve of the cracked TT-joint is recorded during the test. In conjunction with the finite element analysis results, it is found that the bearing capacity of the cracked TT-joint decreases about 28.1% as compared to the corresponding uncracked joint, and it is smaller than the value of 34.5% predicted by using the strength reduction factor F AR recommended in BS7910:2013 + A1:2015 code of practice. Highlights: Carry out fatigue test on a multi-planar CHS TT-joint. Measure hot spot stress distribution of the TT-joint. Record the crack propagation data of the TT-joint. Investigate the failure load of the cracked multi-planar CHS TT-joint.